Short Communication: Diversity, abundance, and utilization of bivalves on the south coast of Pamekasan, Madura Island, Indonesia - EKA RESI KURNIAWAN; RENI AMBARWATI; NUR ROHMATIN ISNANINGSIH (Society for Indonesian Biodiversity, 2024)
Abstract. Kurniawan ER, Ambarwati R, Isnaningsih NR. 2024. Short Communication: Diversity, abundance, and utilization of bivalves on the south coast of Pamekasan, Madura Island, Indonesia. Biodiversitas 25: 2454-2462. Bivalves are a group of mollusks that include clams, oysters, scallops, and mussels. Bivalves have vital roles both economically and ecologically. This study aims to analyze the diversity and abundance of bivalves in the intertidal zone of south coast of Pamekasan, Madura Island, Indonesia. Sampling was carried out at the lowest tide using the line transect method at four research stations located at Talang Siring Beach and its adjacent areas. Identification was conducted based on morphological characteristics. The data were analyzed descriptive-quantitatively. The results showed that in south coast of Pamekasan, there were 21 species of bivalves belonging to 13 genera and 8 families. The value of diversity index was 2.21 which included in the medium category. The results of the bivalve community index stated that the station 3 had the highest diversity value among other sampling stations, which was 2.2. The highest relative abundance value was found in the species Tellinides timorensis Lamarck 1818 which was 35.96%. Among the 21 species found at Talang Siring Beach and its adjacent areas, nine of them are frequently utilized by local people. Although Talang Siring Beach is managed as a tourism area, this beach is a potential habitat for bivalves.